Exploring the external factors affecting the effectiveness of internal audit in Moroccan public enterprises with commercial activities: A qualitative approach - GHARRAFI, Mehdi; FELLAH, Ismail BEL; LOUBNA, ASSAIRH; MAHOUAT, Nacer; Abderrahim, BENLAKOUIRI (Edelweiss Applied Science and Technology, 2024)
The aim of this study is to identify the external factors affecting the effectiveness of internal auditing in public companies with commercial activities in Morocco. Using a qualitative methodology based on semi-directive interviews with 24 internal auditors, audit managers and managers, the study explored the challenges faced by these departments. The results highlight several key factors influencing the effectiveness of internal auditing. Top management support is essential to ensure auditors' independence and effectiveness. However, a lack of support from top management limits their ability to conduct effective audits. In addition, the human, financial and material resources allocated to auditing are often insufficient, which affects the quality of assessments. Implementation of audit recommendations is also a weak point: resistance to change and lack of follow-up prevent continuous improvement of practices. Finally, fluid communication between different departments is crucial, but is often hampered by organizational silos, limiting access to the information needed for a complete assessment. To improve the effectiveness of internal auditing, it is therefore necessary to strengthen managerial support, allocate more resources and improve inter-departmental communication and the implementation of recommendations.